Experience, perception and attitude of kindergarten teachers toward shared reading - Yi, Low Wan (Pusat Pengajian Kesihatan, 2015)
Shared reading is an effective reading instruction in classroom to facilitate literacy growth and language development among young children. This current research studied on the perception, experience, and attitude of kindergarten teachers toward shared reading. A total of 41 kindergarten teachers who were teaching at kindergartens in Kubang Kerian, Kelantan had involved in the study. Self-administered questionnaires were used as the research instrument. The data collected were analyzed descriptively in frequency and percentage. Findings disclosed that shared reading was a common reading instruction conducted by the kindergarten teachers in current study. Generally, the kindergarten teachers reported a certain extent of understanding on shared reading and majority of them conducted the shared reading as a reading instruction to improve the students’ language skills, rather than aimed for the literacy growth. The kindergarten teachers reported positive attitude toward the use of shared reading in kindergarten, however, they were lack of training in shared reading as over half of the kindergarten teachers denied their attendance in any shared reading training. These findings suggested that the authority especially Ministry of Education Malaysia could provide training related to shared reading to the kindergarten teachers in order to improve their understanding and skills in conducting shared reading. Speech-language pathologists (SLPs) may play their role to facilitate the practices of kindergarten teachers in shared reading, especially in term of selection of appropriate materials and strategies to teach print concept and language using shared reading. The professional development among kindergarten teachers is important as their perception, practices and attitude upon shared reading contribute huge influences for the outcome of shared reading and consequently, it can influence the benefits obtained, particularly in aspect of language and literacy skill, by the young children through the shared reading.